Hibiscus manihot L. flower extract induces anticancer activity through modulation of apoptosis and autophagy in A549 cells - Minglu Xu; Mengxia Zhao; Miaomiao Zhu; Hongmei Yuan; Zhongzheng Li; Peishuo Yan; Chi Ma; Huabin Zhao; Shenghui Wang; Ruyan Wan; Lan Wang; Guoying Yu (Scientific Reports, 2024)
Abstract Lung cancer is a major public health issue and heavy burden in China and worldwide due to its high incidence and mortality without effective treatment. It’s imperative to develop new treatments to overcome drug resistance. Natural products from food source, given their wide-ranging and long-term benefits, have been increasingly used in tumor prevention and treatment. This study revealed that Hibiscus manihot L. flower extract (HML) suppressed the proliferation and migration of A549 cells in a dose and time dependent manner and disrupting cell cycle progression. HML markedly enhanced the accumulation of ROS, stimulated the dissipation of mitochondrial membrane potential (MMP) and that facilitated mitophagy through the loss of mitochondrial function. In addition, HML induced apoptosis by activation of the PTEN-P53 pathway and inhibition of ATG5/7-dependent autophagy induced by PINK1-mediated mitophagy in A549 cells. Moreover, HML exert anticancer effects together with 5-FU through synergistic effect. Taken together, HML may serve as a potential tumor prevention and adjuvant treatment for its functional attributes.